2020
DOI: 10.21608/ejom.2020.67771
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Awareness and Practice of Ionizing Radiation Protection Procedures Among Exposed Health Care Workers

Abstract: Introduction:Occupational exposure to ionizing radiation is the result of exposure at work sites for diagnostic and therapeutic practices. Ionizing radiation is an energy type in the form of electromagnetic waves or particles. Radiographic imaging is extremely valuable as a diagnostic tool in medical fields leading to different health hazards to health care workers (HCWs) and to the surrounding environment if safety measures are not observed. Aim of work: To assess awareness and practice of ionizing radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…16 In contrast, some previous studies have shown that there were significant differences between radiation protection practice and age, 18 gender, 19 education, 18 occupation, 19 and working experience. 18,20 In the present study, however, there was no significant difference according to the participants' experience, age, gender, or frequency of imaging examination. The reason for this difference was unclear, and further studies may be necessary to clarify the significant factors affecting the appropriate acts of the professionals in the radiology department.…”
Section: Discussioncontrasting
confidence: 61%
“…16 In contrast, some previous studies have shown that there were significant differences between radiation protection practice and age, 18 gender, 19 education, 18 occupation, 19 and working experience. 18,20 In the present study, however, there was no significant difference according to the participants' experience, age, gender, or frequency of imaging examination. The reason for this difference was unclear, and further studies may be necessary to clarify the significant factors affecting the appropriate acts of the professionals in the radiology department.…”
Section: Discussioncontrasting
confidence: 61%
“…Radiologists wearing aprons in this study were only 45%, which could be explained by the lack of health instructions and supervision of workers to decrease the risks of exposure to ionizing radiation. A recent study of 195 radiologists to assess awareness and practice of ionizing radiation protection procedures among health-care workers (HCWs) occupationally exposed to ionizing radiation at Zagazig University Hospitals revealed that satisfactory awareness of radiation protection procedures among HCWs was 51.3%, but HCWs had inadequate practice scores (only 18%) regarding the use of safety measures of radiation exposure during work (Salah Eldeen and Farouk, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 During the last decade, many studies in different countries have been conducted to analyse the knowledge of medical workers about the issue of radiation safety. [32][33][34][35][36][37][38] Many of them showed unsatisfying results. For example, there was realized an Italian study that used the questionnaire method.…”
Section: Role Of Public Health In Radiation Safety Of the Medical Workersmentioning
confidence: 99%